Parametric study using distributed computing and genetic algorithm in TFT‐LCD projector. Issue 11 (21st February 2014) - Lin, Samuel I‐En; Lin, S. C.; Lo, Yun‐Chien
Abstract We present an analysis of the parameters affecting light engines in liquid crystal display (LCD) projectors, using actual LCD projectors as examples. The significant parameters affecting light engines in LCD projectors are evaluated using the light uniformity as the determining standard. Optimization is performed on those parameters that affect the uniformity as well as the rendering effects of the projectors, by employing our own distributed genetic algorithm. The rotation angle of the collimator and its position are shown to improve the uniformity of the LCD projection, but we find that their effect on improving the brightness is not significant. Increased length of a projectors' light tube promotes better integration results. In our study, we effectively improved the performance index of an LCD projector, increasing projection uniformity by 4% (to 91.5%) and the brightness by 12% (to 7.9 lm).